Strategic Soft Skills Development as a Driver of Employee Performance: A Study in the Manufacturing Sector - Hidayati, Rizka Maulidta; Anshori, Yusak (Journal of Entrepreneurship & Technopreneurship, 2026)
In improving employee performance, one way that can be done by the company is by holding training and development of soft skills. Training is a learning process designed to improve the knowledge, skills, and competence of individuals in a particular field, the training itself has the aim of improving and developing employee attitudes, behavior, and skills. While soft skills are non-technical abilities related to how a person interacts and collaborates with others. Soft skills include various interpersonal, communication, and emotional abilities that aim to improve individual effectiveness in working, build good relationships with teamwork, and create a productive and harmonious work environment. This study aims to determine the effect of training and development of soft skills on the performance of CV Dwi Pelita Mas employees. The method in this study uses a quantitative method by distributing questionnaires with a sample or research respondents totaling 35 employees of CV Dwi Pelita Mas. The results of this study indicate that training and development of soft skills have a significant positive effect on the performance of CV Dwi Pelita Mas employees.